Transvertebral magnetic neuromodulation for the treatment of overactive bladder: 6 months follow-up - G V. Kovalev; D. D. Shkarupa; N. D. Kubin; A. O. Zaitseva; I. V. Borodulina; P. E. Musienko (Вестник урологии)
Introduction. The most common type of lower urinary tract dysfunction is an overactive bladder (OAB). Today there is a need to search for new effective methods of treating this disease.Purpose of the study. To evaluate the effectiveness of transvertebral magnetic neuromodulation (TMN) of the lumbar spine in patients with OAB.Materials and methods. 26 patients were enrolled in the clinical study. The treatment course consisted of 15 procedures (3 times a week for 5 weeks). Before and after treatment at 1, 3 and 6 months, complaints were assessed using the ICIQ-SF and OAB-q SF questionnaires. Objective parameters were assessed by urodynamic tests before and 6 months after treatment.Results. We observed a significant improvement in patients subjective clinical status at all points of assessment. Transvertebral magnetic neuromodulation had the greatest influence on such urodynamic parameters as the first sensation, the first desire, strong desire, maximum cystometric capacity. Patterns of phase hyperactivity were absent in 60.8% of patients after treatment and terminal hyperactivity in 41.7% of patients.Conclusions. This small study observed a significant therapeutic effect of TMN in patients with OAB. Further large placebo-controlled trials are needed to develop universal effective protocols for lower urinary tract dysfunction treatment.